2020
DOI: 10.1186/s12913-020-05752-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer pathology services in sub-Saharan Africa: a survey within population-based cancer registries

Abstract: Background Pathologists face major challenges in breast cancer diagnostics in sub-Saharan Africa (SSA). The major problems identified as impairing the quality of pathology reports are shortcomings of equipment, organization and insufficiently qualified personnel. In addition, in the context of breast cancer, immunohistochemistry (IHC) needs to be available for the evaluation of biomarkers. In the study presented, we aim to describe the current state of breast cancer pathology in order to highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…Non-availability of reliable immunohistochemistry (IHC) is a major hindrance to provide tailored breast cancer management in most LMICs. A recently published survey among the laboratories from 17 countries participating in the African Cancer Registry Network (AFCRN) observed that only half of these laboratories had IHC facilities [ 21 ]. The sub-optimal quality of IHC at such laboratories is evident from the unusually high (as much as 50%) frequency of triple-negative breast cancers reported in African studies [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-availability of reliable immunohistochemistry (IHC) is a major hindrance to provide tailored breast cancer management in most LMICs. A recently published survey among the laboratories from 17 countries participating in the African Cancer Registry Network (AFCRN) observed that only half of these laboratories had IHC facilities [ 21 ]. The sub-optimal quality of IHC at such laboratories is evident from the unusually high (as much as 50%) frequency of triple-negative breast cancers reported in African studies [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some of the registry areas included in this study, there was only 1 (Addis Ababa, Cotonou) or no (Bamako) laboratory with immunohistochemistry facilities for HRS testing. 23 The NCCN Harmonized Guidelines for SSA 9 present the standard-of-care situation with the availability of HRS and do not make recommendations for treatment when the HRS is unknown. Previous recommendations have suggested giving endocrine therapy to women with locally advanced BC even with unknown HRS.…”
Section: Main Findings In the Context Of Previous Studiesmentioning
confidence: 99%
“… 42 Lack of pathologists, logistical support, and standardization of tests continue, however, to hinder quality cancer management and research output. 43 , 44 Core biopsy utilization and improved reporting turnaround in SSA indicate attempts at standardization. The mean turnaround time for pathology reporting in high-income countries, South Africa, and Botswana is 4, 16 (± 11), and up to 57 days, respectively.…”
Section: Discussionmentioning
confidence: 99%